2015
DOI: 10.4239/wjd.v6.i3.445
|View full text |Cite
|
Sign up to set email alerts
|

New-onset diabetes mellitus after kidney transplantation: Current status and future directions

Abstract: A diagnosis of new-onset diabetes after transplantation (NODAT) carries with it a threat to the renal allograft, as well as the same short- and long-term implications of type 2 diabetes seen in the general population. NODAT usually occurs early after transplantation, and is usually diagnosed according to general population guidelines. Non-modifiable risk factors for NODAT include advancing age, African American, Hispanic, or South Asian ethnicity, genetic background, a positive family history for diabetes mell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 92 publications
3
81
0
1
Order By: Relevance
“… recently reported that IL2R‐Abs and TMG were similar with respect to risk for overall cancer and viral‐related cancer, but TMG had a slightly higher risk for melanoma. The risk for NODAT has been shown in prior studies to increase with the use of Tac and with steroids ; consistently, we observed a reduced NODAT risk with CsA‐based and steroid‐free ISx compared with the reference regimen. We also observed a higher risk of NODAT when a three‐drug maintenance regimen of Tac + MPA/AZA + Pred was used without induction.…”
Section: Discussionsupporting
confidence: 79%
“… recently reported that IL2R‐Abs and TMG were similar with respect to risk for overall cancer and viral‐related cancer, but TMG had a slightly higher risk for melanoma. The risk for NODAT has been shown in prior studies to increase with the use of Tac and with steroids ; consistently, we observed a reduced NODAT risk with CsA‐based and steroid‐free ISx compared with the reference regimen. We also observed a higher risk of NODAT when a three‐drug maintenance regimen of Tac + MPA/AZA + Pred was used without induction.…”
Section: Discussionsupporting
confidence: 79%
“…Mechanistically, rapamycin is an immunophillin that functions as an mTOR inhibitor only when bound to FKBP12. Patients on rapamycin often development new onset diabetes after transplantation (NODAT), which can increase post-transplant morbidity and mortality [159, 160]. The exact mechanisms by which NODAT develops is not understood [160162].…”
Section: In the Clinic: Mtor-targeted Therapies And The Role Of Adipomentioning
confidence: 99%
“…However, published and personal experience suggest that TAC can be a good alternative to CsA in adolescents, especially girls, as it does not induce hypertrichosis or gingival hypertrophy, side effects to which these patients are very sensitive, thus improving therapeutic compliance. An oral glucose tolerance test before starting is prudential (52).…”
Section: Nonsteroidal Immunosuppressive Drugsmentioning
confidence: 99%